Alfabetização financeira: uma análise do conhecimento, atitude e comportamento financeiro da sociedade brasileira - Souza, Maria Cecília da Cruz (2023)
Financial literacy is a combination of awareness, knowledge, skill, attitude, and behavior necessary for individuals to make financial decisions to comply with citizens' duties towards society and achieve financial well-being. Because of this, society must be composed of citizens with such knowledge since financial literacy in a population is one of the main factors that strengthen a country's economy. The main objective of this research is to understand and analyze the behavior, skill level, and financial attitude of Brazilian society, in addition to understanding the role and need of the state to invest in financial education. It is also worth mentioning that this analysis should be studied based on the socioeconomic variables of society to make a comparison